The role of transcription factor FoxP3 as a predictor of acute and chronic urticaria in children - S. V. Maltsev; L. P. Sizyakina; A. A. Lebedenko (Медицинский вестник Юга России, 2021)
Objective: To study the transcription factor FoxP3 in children with acute and chronic spontaneous urticaria as a possible predictor of the severity and chronicity of urticaria.Materials and Methods: A total of 264 children of both sexes aged from 6 to 16 years old with diff erent variants of urticaria course were examined. Clinical methods of the study included the analysis of anamnestic data and an objective examination of the child with the determination of the severity of urticaria. Immunological methods of the study included the identifi cation of T-regulatory lymphocytes with the CD4+CD25+ Foxp3+CD45+immunophenotype.Results: A signifi cant decrease in the level of transcription factor FoxP3 was found in children with severe acute urticaria and chronic urticaria compared to the control group.Conclusion: Th e degree of reduction in the level of FoxP3 signifi cantly aff ected the likelihood of the development of a severe course of acute urticaria and possible chronization of the disease.